The role of intramyocellular lipid content in the physiological changes observed in inactivity, exercise, and non-alcoholic fatty liver disease - Chivaka, Prince (2023)
Lipid stored within droplets in skeletal muscle, referred to as intramyocellular lipid (IMCL), has established and emerging roles in health and disease. Lipid droplets (LDs) act as the first destination for activated fatty acids (FAs) following their esterification to triacylglycerol (TAG). Under normal physiological conditions these FAs are then released from LDs to supply adjacent mitochondria with substrate for ATP production during fasting and exercise. It has been proposed that dysregulation of adipose tissue storage, in the context of chronic overfeeding, and basal and insulin-mediated impairments in muscle lipid oxidation in response to inactivity are responsible for the ectopic accumulation of lipid in the skeletal muscles. This accumulation can result in increased sarcoplasmic and sarcolemmal expression of intermediates of TAG synthesis and lipolysis, which attenuate the insulin signalling pathway, resulting in skeletal muscle and whole-body insulin resistance, and potentially contributing to the aetiology of non-alcoholic fatty liver disease (NAFLD). However, the associations between IMCL accumulation and insulin resistance in inactivity and NAFLD are equivocal, and the adaptations in IMCL to resistance exercise training are poorly defined. Therefore, primarily using the hyperinsulinaemic-euglycaemic clamp technique, the gold standard method in the assessment of insulin action in humans in vivo, and histochemical quantification of total and fibre-type specific IMCL content, the results of the work in this thesis contribute to our understanding of the role of IMCL in inactivity, resistance exercise training, and NAFLD. This thesis comprises primarily of retrospective analyses of four comprehensive human volunteer studies. The studies described in Chapter 3 explored the role of IMCL in the development of whole-body insulin resistance during acute (3 days) and chronic (56 days) bed rest in healthy, male participants maintained in energy balance throughout. Glucose disposal was decreased by a similar magnitude after 3 and 56 days of bed rest, and these observations could not be explained by IMCL accumulation. This suggests that inactivity per se is the primary driver of whole-body insulin resistance during bed rest and that IMCL accumulation is likely to be a confounding response that occurs when participants are in positive energy balance. It has been proposed that overfeeding, which contributes to the pathogenesis of obese NAFLD by increasing plasma FA concentration and hepatic lipid content, also leads to the ectopic accumulation of IMCL. Given that the skeletal muscles are the main sites for the disposal of glucose and that IMCL accumulation is associated with muscle insulin resistance, increased muscle lipid content may contribute to the development of whole-body insulin resistance in those with NAFLD. The study described in Chapter 4 investigated differences in IMCL content, skeletal muscle glucose disposal, and whole-body glucose disposal between individuals with NAFLD and healthy controls to determine if muscle lipid content does in fact contribute to insulin resistance in those with NAFLD. It was observed that IMCL content was not different between healthy males and males with NAFLD, even though skeletal muscle and whole-body glucose disposal were significantly reduced in those with NAFLD. These findings suggest that IMCL accumulation is not a contributor to the development of insulin resistance in NAFLD. The study described in Chapter 5 explored changes in IMCL and perilipin 5 (PLIN5) content in response to a 12-week resistance training intervention, which has not been investigated in detail to date. A secondary aim was to determine the impact of the non-steroidal anti-inflammatory drug (NSAID), diclofenac, on the mRNA expression of genes involved in FA metabolism and oxidation. It was hypothesised that diclofenac would have a role in these processes based on evidence of its affinity for Peroxisome proliferator-activated receptor gamma (PPAR-γ) in vitro. This study comprised a randomised, placebo controlled, double-blind protocol in which one group of exercise-trained participants ingested diclofenac, 75 mg/daily, concurrent with the exercise protocol. IMCL content and muscle PLIN5 content did not change in response to the resistance exercise intervention, though diclofenac administration robustly altered the mRNA expression of genes involved in lipid metabolism. This thesis presents novel insights into the role of IMCL content in the development of insulin resistance in the context of bed rest-induced immobilisation and NAFLD. It also identifies a new trajectory for future research into diclofenac, an NSAID which may alter muscle FA oxidation via a previously underexplored mechanism.